The morphotropic phase boundary and electrical properties of (1 - X)Pb(Zn1/2W1/2)O3-xPb(Zr0.5Ti0.5)O3ceramics - O. Khamman (2018)
Ceramics in the solid solution of (1 - x)Pb(Zn1/2W1/2)O3-xPb(Zr0.5Ti0.5)O3system, with x = 0.80, 0.85, 0.90, and 0.95, were synthesized with the solid-state reaction technique. The perovskite phase formation in the sintered ceramics was analyzed with X-ray diffraction. It shows that the rhombohedral and the tetragonal phases coexist in the ceramic with x = 0.90, indicating the morphotropic phase boundary (MPB) within this pseudo-binary system. Dielectric and ferroelectric properties measurements indicate that the transition temperature decreases while the remanent polarization increases with the addition of Pb(Zn1/2W1/2)O3. In the composition of x = 0.85 which is close to the MPB in the rhombohedral side, a high piezoelectric property with d33= 222 pC/N was observed. © 2009 Springer Science+Business Media, LLC.